2019
DOI: 10.1111/apt.15456
|View full text |Cite
|
Sign up to set email alerts
|

Infliximab induction regimens in steroid‐refractory acute severe colitis: a multicentre retrospective cohort study with propensity score analysis

Abstract: Summary Background Accelerated induction regimens of infliximab have been proposed to improve response rates in patients with steroid‐refractory acute severe colitis. Aim To determine the differences in outcome for acute severe ulcerative colitis between accelerated and standard‐dose infliximab Methods We collected data on hospitalised patients receiving differing regimens of rescue therapy for steroid‐refractory acute severe ulcerative colitis. Our primary outcome was 30‐day colectomy rate. Secondary outcomes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
23
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 29 publications
0
23
0
1
Order By: Relevance
“…Chedid and Kane for their thoughtful editorial 1 on our paper evaluating the impact of accelerated induction in corticosteroid-refractory acute severe colitis. 2 We agree that, in the absence of results from an adequately powered RCT, propensity score matching analysis of cohort studies is useful to identify clinical benefits when therapeutic decisions are very heterogenous. We also agree that almost all of the cohort studies so far have not reported data to support the use of accelerated induction dosing regimens despite compelling pharmacokinetic and pharmacodynamic data.…”
mentioning
confidence: 77%
“…Chedid and Kane for their thoughtful editorial 1 on our paper evaluating the impact of accelerated induction in corticosteroid-refractory acute severe colitis. 2 We agree that, in the absence of results from an adequately powered RCT, propensity score matching analysis of cohort studies is useful to identify clinical benefits when therapeutic decisions are very heterogenous. We also agree that almost all of the cohort studies so far have not reported data to support the use of accelerated induction dosing regimens despite compelling pharmacokinetic and pharmacodynamic data.…”
mentioning
confidence: 77%
“…Laharie and Riviere for their thoughtful comments on the use of infliximab rescue therapy and accelerated induction in the setting of steroid-refractory acute severe colitis as reported in our recent paper. 1,2 I fully appreciate their own observation 3 that the 1-year colectomy rates have not declined based on randomised controlled trial evidence.…”
mentioning
confidence: 96%
“…The multicentre retrospective study conducted by Sebastian et al , provides additional information on this pending question. It showed that patients treated with intensified doses had higher initial C‐reactive protein (CRP) levels and lower albumin levels but similar colectomy rates at 1 year than patients receiving the standard induction regimen . Their results illustrate that physicians have already integrated biomarkers into their daily management of patients admitted for ASUC.…”
mentioning
confidence: 99%